Application of Role Playing Learning Model To Improve Science Learning Outcomes - Lamiada Lamiada (USN Scientific Journal, 2022)
This research was motivated by the low science learning outcomes of class VI students at SD Negeri 66 Mambo with an average class score of 67.14. Therefore, researchers provide learning alternatives by applying the role-play learning model in class VI SD Negeri 66 Mambo. This research aims to improve Science learning outcomes for class VI students at SD Negeri 66 Mambo by applying for the Role Playing Learning Model. The form of research conducted was Classroom Action Research (CAR) with 2 cycles. Based on the analysis of research data after applying for the Role Playing learning model, the average percentage of teacher activity in cycle I was 62.5% increasing to 85.25% in cycle II. The average percentage of student activity also increased, namely 50% in cycle I increased to 83.3% in cycle II. Student learning outcomes on the basic score with a class average of 67.14 with a completeness percentage of 50% and in cycle I experienced an increase with an average class score of 75.17 with a percentage increase in learning outcomes of 11.96% and the percentage of students who completed 57 .14%. Then in cycle II, the class average score increased to 87.85 with a percentage increase in learning outcomes of 30.84% and the percentage of students who completed was 85.71%, after the Role Playing learning model was applied. The results of this study indicate that the application of the role-play learning model can improve science learning outcomes for class VI students at SD Negeri 66 Mambo.